Modernity in black and white : art and image, race and identity in Brazil, 1890-1945 - Cardoso, Rafael (Afro-Latin America, 2021)
Introduction. Ambiguous modernities and alternate modernisms -- Heart of darkness in the bosom of the modern metropolis : favelas, race and barbarity -- A pagan festival for the up to date : art, bohemianism and carnival -- The printing of modern life : a new art for a new century -- The cosmopolitan savage : modernism, primitivism and the anthropophagic descent -- The face of the land : depicting 'real' Brazilians under Vargas -- Epilogue. Images of a culture at war with itself.